Teachers’ Awareness and Inclusive Education of Children with Disabilities in Primary Schools in Tororo District - Kaggwa, Rosette Victoria Tamale; Othieno, Gerald (Direct Research Journal of Social Science and Educational Studies, 2024)
This study examined Teachers’ teachers’ awareness and knowledge towards inclusive education of children with disabilities. Across sectional survey design involving both quantitative and qualitative approaches was used to gather data from 79 respondents who included teachers and Head teachers in inclusive primary schools in Tororo District. The head teachers were selected purposively while for the teachers; simple random sampling technique was used. The study used questionnaire and interview to collect data from teachers and head teachers respectively. The study finding shows that teachers’ awareness was significantly related to inclusive education of learners with different categories of disabilities in primary schools in Tororo District. It was thus concluded that teachers’ awareness enhance inclusion in education of learners with different categories of disabilities in primary schools in Tororo District. The study recommended the following: The government through the Ministry of Education and Sports should harness change of attitude of various stake holders by sensitizing them about the benefits of inclusion of learners with disabilities in education. Teacher training institutions such as colleges and universities should equip teacher trainees with skills and knowledge in inclusive education pedagogies and practice. The school administrators in should admit all children including those with disabilities in schools without discrimination. Refresher courses and seminars should be conducted to equip teachers with skills in teaching children with different forms of disabilities. The government should invest more in provision of accessible disability friendly learning environment and adapted specialized educational materials to facilitate inclusive learning in schools.